2013
DOI: 10.1111/ics.12061
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the origins of nanostructural variations in differential ethnic hair types using X‐ray scattering techniques

Abstract: The results indicate that the fibrous keratin scaffold remains consistent between ethnic hair types. The hierarchies made by these may be modulated by variation in the content of keratin-associated proteins (KAPs) and lipids that alter the interfacial structures and lead to macroscopic differences in hair morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 21 publications
1
21
0
2
Order By: Relevance
“…It also supports our hypothesis that wool and hair contain two cortical cell groups with two subgroups each. These considerations are in agreement with various views in the literature but in contrast to, for example, those of Leon…”
Section: The Role Of Cell Group Segregationsupporting
confidence: 92%
“…It also supports our hypothesis that wool and hair contain two cortical cell groups with two subgroups each. These considerations are in agreement with various views in the literature but in contrast to, for example, those of Leon…”
Section: The Role Of Cell Group Segregationsupporting
confidence: 92%
“…15,16 Studies with X-ray scattering analysis did not observe any differences in the structures and configurations of the proteins (α-helical arrangements, coiled-coil structures, IF, and macrofibrils) across major biogeographic origins. 3,14 In addition, the differences between wet and dry states among hair types observed from the lipid diffraction via X-ray scattering analysis indicated a variation of crystalline lipid structures among different hair origins. 14…”
Section: Cortexmentioning
confidence: 99%
“…3,14 In addition, the differences between wet and dry states among hair types observed from the lipid diffraction via X-ray scattering analysis indicated a variation of crystalline lipid structures among different hair origins. 14…”
Section: Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in hair properties depending on ethnicity have been widely studied [1][2][3][4][5][6][7][8][9][10][11][12]. These studies have revealed the unique hair properties (such as shape, curliness, color, follicle, mechanical behavior, damage mechanism, etc.)…”
Section: Introductionmentioning
confidence: 99%